(untitled) (Stato, Chiese e pluralismo confessionale, 2024)
Status and current perspectives on debt ABSTRACT: Ours is a world balanced precariously between hopelessly opposing forces. In such a world the long-standing and noble battle for the elimination of illegitimate debt has little hope of success. Action must be taken on the causes but do we have the capacity and the tools? This question is attempted to be answered in the five paragraphs of this update article, reiterating with further arguments the need for the United Nations General Assembly to request an advisory opinion from the International Court of Justice on the consistency and adequacy of existing rules. It is appropriate to refer for the premises to an earlier article on the subject, entitled Holy See and illegitimate debt. The path to the International Court of Justice (2015-2022). SOMMARIO: 1. Coltivare la speranza in un mondo migliore - 2. L’alternativa alla violenza nella svolta latinoamericana - 3. L’improbabile via statunitense - 4. La via italiana oggi - 5. Esiste un futuro per la via africana sul debito?